Cough symptoms in children following COVID-19: a single-center retrospective study - Liu, Ling; Zhang, Lu; Zhou, Pengxiang; Zhou, Wei; Li, Linghui; Zeng, Lin; Li, Nan; Zhao, Rongsheng; Han, Tongyan (Frontiers in Pediatrics, 2024)
Background: Cough is the most common respiratory symptom in children with mild coronavirus disease 2019 (COVID-19); however, evidence regarding the duration and severity of COVID-19-related cough is sparse. Herein, we investigated the correlation between cough severity/duration and disease duration in children with allergic diseases following COVID-19. Methods: This single-center, retrospective case-control study was conducted at the Department of Pediatrics, Peking University Third Hospital, from February 6–13, 2023. Children aged 0–16 completed a questionnaire survey collecting basic information and weekly cough scores for 8 consecutive weeks after COVID-19 in December 2022. The Kaplan–Meier method was used to draw event curves, and the log-rank method was used to compare inter-group differences. Stepwise regression was applied for multivariate analysis of correlations between age, sex, allergic diseases, and the degree and duration of cough following COVID-19. Results: Overall, 686 children were included, of whom 183 (26.7%) had allergic diseases and 503 (73.3%) did not. Kaplan–Meier analysis identified significant differences between patients with and without allergic disease (log-rank test, P=0.002) and between patients with no allergic disease and those with one and more than one allergic disease (log-rank test, P=0.003). Multivariate regression identified a link between the presence of more than one allergic disease and coughing for >4 weeks after infection (P<0.001). Allergic disease was the primary factor linked to cough symptoms lasting 8 weeks and cough severity (P<0.001). Conclusions: Allergic disease contributes to the prolonged duration and severity of coughing in children with mild COVID-19.